2018
DOI: 10.25135/rnp.11.17.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compositions of Achillea sivasica: Different Plant Part Volatiles, Enantiomers and Fatty Acids

Abstract: In the present work, Microsteam distillation -Solid phase microextraction (MSD-SPME) and hydrodistillation (HD) techniques were applied to obtain volatiles from Achillea sivasica, an endemic species from Turkey. GC-FID and GC/MS analysis revealed that 1,8-cineole (22.1%) and -pinene (9.3%) were the main constituents of the hydrodistilled flower volatiles. (Z)--Farnesene (23.9%), decanoic acid (10.1%), eudesmol (8.0%), tricosane (7.3%) and hexadecanoic acid (7.2%) were the main volatiles obtained from flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Previous researches indicated that volatile oils extracted from some Achillea species were represented by the high content of monoterpene oxygenated . The percentages of sesquiterpene oxygenated ranged from 0.33 to 0.79 %, sesquiterpene hydrocarbons were represented by 0.24 to 4.81 %.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous researches indicated that volatile oils extracted from some Achillea species were represented by the high content of monoterpene oxygenated . The percentages of sesquiterpene oxygenated ranged from 0.33 to 0.79 %, sesquiterpene hydrocarbons were represented by 0.24 to 4.81 %.…”
Section: Resultsmentioning
confidence: 97%
“…When all periods were compared, the accumulation of menthone and menthol were highest in the samples harvested at 8 pm (22.78 % and 20.55 %, respectively). Many studies conducted previously in medicinal plants have shown that factors such as, genetics, environmental conditions, postharvest treatments, harvesting times and phenological stages are effective in the change of volatile oil composition …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction of fatty acids from T. decipiens has been carried out using the "Fatty Acid Extraction" Kit. Methyl esters of the fatty acids were obtained with Boron trifluoride-methanol solution and analyzed by GC-FID/MS (28). In vitro AChE and -amylase enzyme inhibitions of the extracts were determined by spectrophotometric method with Ellman's and KI/I2 reagents, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were carried out on Achillea taxa by both local and foreign workers on different aspects, mostly on chemical components and their importance for anticancer, antimicrobial etc. (Tabanca et al 2016, Haliloğlu et al 2017, Demirci et al 2018, Özek et al 2018. Studies on morphology, anatomy and palynology of A. ketenoglui H. Duman are still limited (Arabacı 2006, Akyalçın et al 2009, 2011, 2014, Grytsyk 2016, Dauti et al 2017).…”
Section: Introductionmentioning
confidence: 99%